Genitoplastia feminizante, pela técnica de mobilização do seio urogenital, em meninas com hiperplasia adrenal congênita - Luis Henrique Perocco Braga (2008)
Purpose: To evaluate the outcomes of feminizing genitoplasty using urogenital sinus mobilization for congenital adrenal hyperplasia, with particular attention to genital appearance and urinary continence. Patients and Method: This study was made in two stages: in the first one, 10 patients were treated with total urogenital sinus mobilization. Patient age at operation ranged from 11 to 78 months (mean = 32 months) and the follow-up from 15 to 36 months (mean = 26 months). In the second stage, we conducted a prospective evaluation of 24 girls who underwentfeminizing genitoplasty using partial urogenital sinus mobilization with preservation of the pubourethral ligaments during a 4-year period. Patient age at operation ranged from 1 month to 16 years (median 28.5 months), with a mean followup of 25 months (8 a 47 months). Urogenital sinus length determined by cystoscopy and degree of external genitalia virilization, defined according to Prader classification, were evaluated before reconstruction. Degree of virilization was Prader type III in 3children (12.5%), type IV in 16 (66.7%) and type V in 5 (20.8%). At follow-up patients were examined while under sedation for evaluation of overall external genitalia cosmesis and calibration of the vagina. Urinary continence status and voiding efficiency were assessed clinically in toilet trained patients by voiding diary, and measurement of bladder capacity and post-void residual by ultrasound. Results: In the first study, cosmetics results were good in 7 patients with vaginal and urethral openings separated at the surface of the vestibule, and satisfactory in3. All girls had urinary continence. In the second, cosmetic results were good in 21 patients (87.5%) and satisfactory in 3 (12.5%). The vaginal and urethral openings were separate and identified at the surface of the vestibule in 21 girls. Adequate caliber of the mobilized vagina was achieved in 23 patients (95.8%). None of the 20 toilet trained patients had urinary incontinence or recurrent urinary tract infections, with normal bladder emptying in 18 and post-void residual in 2 (10%). Conclusions: Both total and partial urogenital sinus mobilization resulted in goodcosmetic appearance and preserved urinary continence in most girls withcongenital adrenal hyperplasia and urogenital sinus anomaly.